Association of the IRAK4 rs4251545 genetic polymorphism with severity of enterovirus‐71 infection in Chinese children - Jie Song; Yedan Liu; Ya Guo; Peipei Liu; Fei Li; Chengqing Yang; Xiaoyu Pan; Liping Yi; Fan Fan; Han Zhao; Zongbo Chen (Immunity, Inflammation and Disease, 2022)
Abstract Introduction This study aimed to explore the association between the IRAK4 polymorphism rs4251545 and the severity of enterovirus 71 (EV71) infection in Chinese children. Methods We analyzed the IRAK4 polymorphism rs4251545 in 617 EV71‐infected patients and 410 controls using the improved multiplex ligation detection reaction. IRAK4 mRNA expression was tested by qRT‐PCR. Serum concentrations of IL‐6 and NF‐κB were detected using ELISA. Results The frequencies of the GA + AA genotype and A allele in the mild EV71 infection group and in the severe EV71 infection group were significantly higher than those in the normal control group. The frequency of the GA + AA genotype and A allele in severely infected EV71 patients was markedly higher than that in mildly infected EV71 patients. IRAK4 mRNA expression in mildly infected EV71 patients and severely infected patients was significantly higher than that in the control group. IRAK4 mRNA expression in GA + AA genotypes in both mild and severe EV71 infection groups was significantly higher than that in patients with the GG genotype. IL‐6 concentration and the ratio of IL‐6/NF‐κB in severe EV71 cases were significantly lower in patients with the GA + AA genotype than in those with the GG genotype. The ratio of IL‐6/NF‐κB was distinctly higher in severely infected EV71 patients than in mildly infected and control subjects. Conclusions The IRAK4 polymorphism rs4251545 was associated with the susceptibility and severity of EV71 infection. The A allele is a susceptible factor in the development of severe EV71 infection in Chinese children.